User involvement and the NHS reforms - Rhodes, Penny (Health Expect, 2002)
The policy of `user involvement' in the UK National Health Service emerged during the 1990s along with the reforms that created an internal market. Despite the official rhetoric, progress has been limited. Critics suggest that, not only was the policy flawed in its conception by the construction of service users as consumers and the conflation of consumerism with empowerment, but collaborative models of involvement have tended to legitimate rather than challenge existing provision. Some commentators have questioned the value of user involvement initiatives and proposed that alternative approaches, such as a strengthening of procedural rights or alignment with broader political campaigns, would be more appropriate. The low prominence given in the recent Government White Paper The New NHS (1) to the contribution of service users, however, represents less of an ideological shift than a concentration on other, in the Government's view, more pressing priorities: namely, a concern to address the problems of public legitimacy and low staff morale by engaging in greater public participation and giving health professionals a more central role. The result has been a weakening of the users' voice by a conflation of user involvement with public participation and giving health professionals the authority to define users' needs for them. Service users risk, not only having their contribution devalued, but losing the right to an independent and distinctive voice. There is a real danger that the issues of user involvement will not be included on local agendas and the disparities between provision and need and between professionals' and users' views will increase.